Dark‐coloured semen in nonobstructive azoospermia: a report of four cases. (28th February 2013) - Halder, A.; Jain, M.; Chaudhary, I.; Kumar, G.; Das, T.; Gupta, Y. K.
Summary Dark‐coloured semen is rarely observed in men with nonobstructive azoospermia in absence of genital tract bleeding. Dark‐coloured semen is also observed rarely in men with spinal cord injury with or without genital tract bleeding. However, this condition has not been reported in the literature in absence of genital tract bleeding or spinal cord injury. Here, we report men with nonobstructive azoospermia with dark‐coloured semen and without genital tract bleeding or spinal cord injury. The study included four subjects with dark‐coloured semen. All the samples first investigated for the presence of red blood cells as well as haemoglobin. All the cases were examined in details with seminal, hormonal and genetic parameters. In addition, an elemental electron microscopy and inductively coupled plasma‐atomic emission spectrometry evaluation for heavy metals was performed. The semen parameters showed normal volume, pH, leucocyte count and azoospermia or oligoazoospermia. Dark‐coloured semen specimens contained neither red blood cells nor haeme pigment. Electron microscopy showed presence of platinum in all the cases, whereas inductively coupled plasma‐atomic emission spectrometry revealed increased levels of lead, manganese and nickel in serum as compared to controls. The results indicate dark‐coloured semen may be linked with heavy metals found in seminal cells.